(untitled) - Isaacs, Sally Senzell (Chicago, 2004)
Discover the everyday lives of American Indians living in the East and how and why in the 1830s they were forced from their homelands. Find out what it was like to be captured at home, put in stockades, then made to walk along rough trails to Indian Territ
Keywords: Trail of Tears, 1838-1839,Cherokee Indians,Indians of North America,Hành trình nước mắt, 1838-1839,Người Anh điêng bản xứ,Người Anh điêng Bắc Mỹ; History,History,Lịch sử,Lịch sử; 19th century,Juvenile literature,Thế kỷ 19; Southern States,Southern States